Serum levels of adiponectin and leptin as biomarkers of proteinuria in lupus nephritis. - Valeria Diaz-Rizo; David Bonilla-Lara; Laura Gonzalez-Lopez; Dalia Sanchez-Mosco; Nicte S Fajardo-Robledo; Edsaul E Perez-Guerrero; N Alejandra Rodriguez-Jimenez; A Miriam Saldaña-Cruz; M Luisa Vazquez-Villegas; Eduardo Gomez-Bañuelos; Monica Vazquez-Del Mercado; E German Cardona-Muñoz; et al. (PLoS ONE)
Introduction There are controversial results about the role of serum leptin and adiponectin levels as biomarkers of the severity of proteinuria in lupus nephritis. Objective The aim of this study was to evaluate the relationship between serum leptin and adiponectin levels with severity of proteinuria secondary to lupus nephritis (LN). Methods In a cross-sectional study, 103 women with systemic lupus erythematosus (SLE) were evaluated for kidney involvement. We compared 30 SLE patients with LN, all of them with proteinuria, versus 73 SLE patients without renal involvement (no LN). A comprehensive set of clinical and laboratory variables was assessed, including serum levels of leptin and adiponectin by ELISA. Multivariate analyses were used to adjust for potential confounders associated with proteinuria in LN. Results We found higher adiponectin levels in the LN group compared with the no LN group (20.4 ± 10.3 vs 15.6 ± 7.8 μg/mL; p = 0.02), whereas no differences were observed in leptin levels (33.3 ± 31.4 vs 22.5 ± 25.5 ng/mL; p = 0.07). Severity of proteinuria correlated with an increase in adiponectin levels (r = 0.31; p = 0.001), but no correlation was observed with leptin. Adiponectin levels were not related to anti-dsDNA or anti-nucleosome antibodies. In the logistic regression, adiponectin levels were associated with a high risk of proteinuria in SLE (OR = 1.06; 95% CI 1.01-1.12; p = 0.02). Instead, leptin was not associated with LN. Conclusion These findings indicate that adiponectin levels are useful markers associated with proteinuria in LN. Further longitudinal studies are required to identify if these levels are predictive of renal relapse.